Karikatur Al-Arabiyah Fi Hisab Twitter @cartoon_ar (Dirasah Tahliliyah Tadawuliyah) - Faiq Ilham Rosyadi; Muhammad Luqman Chakim (Institut Agama Islam Negeri (IAIN) Metro, 2020)
This research presents several caricature images with various themes, starting from the issue of resistance between the Muslim Brotherhood and Saudi Arabia. Then there is also about the extreme weather that has hit Saudi Arabia for days, as well as other insinuations that contain the readers' motivation. Through this discussion, the researcher tries to analyze and understand each caricature that is presented in the account. Also through this study, researchers looked for some facts and events that were happening in the State of Saudi Arabia at that time. From that incident, inspiration emerged from a caricature and poured it out through a work called caricature. The purpose of this research is to know and understand well what themes are presented, then to study using illocutionary speech acts based on their types and some using speech acts based on their mode. The theory as a surgical tool in this study uses Searle's speech act theory. Data collection was carried out using observation and note-taking techniques, then all data were put together and analyzed one by one. In illocutionary speech acts, there are five types of speech, namely, assertive, directive, commissive, expressive, and declarative. The results of the analysis of the caricatures found, there are several meanings, namely, assertiveness can mean to state, express opinions, and propose. The directive is also divided into four functions, namely ordering, ordering, and giving advice. Commissive means promise. Then Expressive can mean complaining, blame. And the last declarative changes the utterance word into a speech.